Fracture and deformation behaviors of saturated and dried single-edge notched beam sandstones under three-point bending based on DIC. (February 2022) - Qin, Xiaofeng; Su, Haijian; Feng, Yujie; Zhao, Honghui; Pham, Thi Nhan
Highlights: The deformation characteristics and fracture parameters of saturated and dried SENB sandstone specimens under mixed mode I-II loading were discussed. The evolution of the maximum principal strain field during the fracture process was obtained by DIC. The value of ap calculated by DIC (considering both horizontal and vertical displacements) was used to measure the opening of pre-notch. The post-peak macrocrack propagation was subdivided into stable propagation stage and unstable propagation stage. Abstract: It is of great significance to study the fracture and deformation characteristics of rock with different moisture conditions for the safety assessment of "fragile surface with cracks" in rock engineering such as dams and underground chambers affected by groundwater. Therefore, in this work, three-point bending tests were conducted on single-edge notched beam sandstone specimens with different moisture conditions (natural condition, dried condition, and saturated condition) under complex stress environment. Additionally, the digital image correlation (DIC) method was used to quantitatively research the fracture parameters and deformation behavior of specimens during pure mode I fracture and mixed mode I-II fracture. The results show that (1) the average peak load of dried sandstone is 42.18–116.08% higher than that of saturated sandstone. (2) By increasing the offset distance of the pre-notch (0–72 mm), the specimen is transformed from pure mode I fracture to mixed mode I-II fracture, with an increase in average peak load of 152.83–284.24%. (3) When the pure mode I fracture occurs in saturated sandstone, the fracture toughness is 66.74% of that natural sandstone, which is 46.28% of that dried sandstone. (4) In the mixed mode I-II fracture, the effective fracture toughness of sandstone with a consistent moisture condition is 1.05–1.70 times that of the pure mode I fracture. (5) The fracture toughness of saturated sandstone is most significantly affected by the loading mode. When the offset distance of pre-notch increases from 0 to 72 mm, the average effective fracture toughness increases from 4.324 MPa·mm 0.5 to 7.357 MPa·mm 0.5, increasing by 70.14%. Besides, according to the trend of the ap, which was calculated by the DIC method, the post-peak macroscopic crack propagation is divided into two stages: the post-peak stable propagation stage and the post-peak unstable propagation stage.